Onset and Progression of With-the-Rule Astigmatism in Children with Infantile Nystagmus Syndrome - Wang, Jingyun (Association for Research in Vision and Ophthalmology, Inc., 2010)
PURPOSE. The purpose of this study was to examine the onset and progression of with-the-rule (WTR) astigmatism during the first 8 years of life in children with idiopathic infantile nystagmus syndrome (INS) or INS associated with albinism and to compare their development with that of normal children. Also explored was whether early WTR astigmatism influences emmetropization in children with INS and whether there is evidence of meridional emmetropization. METHODS. Cycloplegic refractions culled from medical records were converted into power vector components: M (spherical equivalent), J(0) (positive J(0) indicates WTR astigmatism), and J(45) (oblique astigmatism). Two diagnostic groups (idiopathic, n = 106; albinism, n = 95) were evaluated and compared with a reference normal group (n = 495). Four age subgroups were evaluated: age≤0.5 year, 0.5<age≤1 year, 1<age≤4 year, and 4<age≤8 year; in the normal group, no data were available for 4- to 8-year-olds. In addition, two longitudinal groups of children with INS (idiopathic, n = 22; albinism, n = 27) were studied. RESULTS. WTR astigmatism was prevalent among children with INS, even during infancy. Both the prevalence and magnitude of WTR astigmatism increased with age in both INS groups. Predicted J(0) from the fitted longitudinal data agreed with cross-sectional data. Moreover, the spherical equivalent of children with INS demonstrated little emmetropization during the first 8 years of life. CONCLUSIONS. Both the cross-sectional and longitudinal data showed that WTR astigmatism was common among children with INS and increased in magnitude with age during the first 8 years of life. Changes observed in meridional refractive error with age were consistent with meridional emmetropization in children with INS and WTR astigmatism.